Defects‐Abundant Ga2O3 Nanobricks Enabled Multifunctional Solid Polymer Electrolyte for Superior Lithium‐Metal Batteries. Issue 24 (20th March 2023) - Li, Huixue; Xu, Xijun; Li, Fangkun; Zhao, Jingwei; Ji, Shaomin; Liu, Jun; Huo, Yanping
Abstract: Polyethylene oxide (PEO)‐based polymer electrolytes with good flexibility and viscoelasticity, low interfacial resistance, and fabricating cost have caught worldwide attention, but their practical application is still hampered by the instability at high voltages and the low ionic conductivity (10 −8 to 10 −6  S cm −1 ). Herein, we rationally designed defects‐abundant Ga2 O3 nanobricks as multifunctional fillers and constructed a PEO‐based organic‐inorganic electrolyte for lithium metal batteries. Due to the abundant O‐defects feature of Ga2 O3 filler, this PEO‐based composite electrolyte not only broadens electrochemical stability window (over 5.3 V versus Li/Li + ) but also in situ forms a Li–Ga alloy and solid electrolyte interphase (SEI) film during the cycling process causing a rapid diffusion of Li + ions. The as‐prepared electrolyte has good interface compatibility with Li metal (without short‐circuiting over 500 h at 0.2 mA cm −2 ) and possesses superior high ionic conductivity. The assembled all‐solid‐state LiFePO4 //Li cells attained an excellent cycling performance of 146 mAh g −1 over 100 cycles at 0.5 C. The XPS analysis reveals that Ga2 O3 nanobricks can form in situ a Li−Ga alloy layer at the polymer/anode interface. This work shed a light on designing high ionic conductivity lithium alloys in the composite electrolyte, which can improve the electrochemical properties of PEO‐based polymer electrolytes. Abstract : Defects‐abundant Ga2 O3 nanobricks were applied as multifunctional fillers to construct a PEO‐based organic‐inorganic electrolyte for lithium metal batteries. Due to the multifunctional feature of Ga2 O3 filler, this composite electrolyte not only broadens the electrochemical stability window but also improved the ionic conductivity and thereby attaining a superior rate capability.